Studi Kualitatif Faktor yang Mempengaruhi Perilaku Makan pada Atlet Non-Elite dengan Riwayat Asupan Defisit Zat Gizi Makro di UKM Basket Universitas Negeri Surabaya - Naufal Adipati Fawwaz; Cleonara Yanuar Dini (Lembaga Pengembangan Kinerja Dosen, 2025)
Deficiency in energy and nutrient intake in athletes can disrupt physiological functions, hinder muscle growth, cause fatigue and illness, and result in suboptimal performance. It is crucial for athletes to carefully manage their food intake during training, competition, and recovery, while also considering eating behaviors that include perception, knowledge, and habits related to food selection and consumption. This study aims to identify the factors influencing eating behaviors in non-elite athletes with a history of macro-nutrient intake deficits in the UNESA Basketball UKM. The research employs a qualitative methodology. Data were collected from key and supporting informants selected based on inclusion criteria established by the researcher. The number of research informants was determined based on the information obtained which was deemed to have reached saturation point, resulting in 7 key informants and 8 supporting informants. The collected data were analyzed through transcription and then categorized into relevant codes and themes. The findings of this study identified two main themes influencing the eating behaviors of non-elite athletes in the UNESA Basketball UKM: internal and external factors. Internal factors, including food preferences, self-discipline, self-confidence, state of mind, gastrointestinal discomfort, body image, sleep time, past eating habits, physical activity level, nutritional knowledge, and food allergies. Meanwhile, external factors include social influence, food availability, food prices, and social media.